Guidelines on Establishing Joint Ventures in Infrastructure Sectors - Planning Commission (Planning Commission, 2009)
Public Private Partnerships (PPPs) are normally governed by an agreement between a private entity and a public entity. Agreements for provision of roads, ports, airports, railways and power transmission systems are thus entered into between the respective public and private entities. These agreements typically contain provisions that determine the user charges, performance standards and other matters affecting the users and the public exchequer. They may also involve transfer of valuable public assets, delegation of the power to collect user charges and payment guarantees constituting a contingent liability for the exchequer. Though a single concession/procurement agreement is the norm for PPP projects, public entities sometimes prefer the joint venture (JV) route which requires them to subscribe to the equity of the selected private entity.
Planning Commission Government of India
Planning Commission Government of India